Distance to Degrees: How College Proximity Shapes Students' Enrollment Choices and Attainment across Race-Ethnicity and Socioeconomic Status - Riley Acton; Kalena E. Cortes; Lois Miller; Camila Morales (Institute of Labor Economics (IZA), 2024)
Leveraging rich data on the universe of Texas high school graduates, we estimate how the relationship between geographic access to public two- and four-year postsecondary institutions and postsecondary outcomes varies across race-ethnicity and socioeconomic status. We find that students are sensitive to the distance they must travel to access public colleges and universities, but there are heterogeneous effects across students – particularly with regard to distance to public two-year colleges (i.e., community colleges). White, Asian, and higher-income students who live in a community college desert (i.e., at least 30 minutes driving time from the nearest public two-year college) substitute towards four-year colleges and are more likely to complete bachelor's degrees. Meanwhile, Black, Hispanic, and lower-income students respond to living in a community college desert by forgoing college enrollment altogether, reducing the likelihood that they earn associate's and reducing the likelihood that they ultimately transfer to four-year colleges and earn bachelor's degrees. These relationships persist up to eight years following high school graduation, resulting in substantial long-term gaps in overall degree attainment by race-ethnicity and income in areas with limited postsecondary access.
Keywords: I21; I23; I24; 330; college accessibility; college proximity; college choices; college enrollment; college attainment; associate's degree; bachelor's degree; college enrollment patterns; two-year colleges; four-year colleges; public postsecondary institutions